2014
DOI: 10.3233/jad-131529
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease and Methanol Toxicity (Part 1): Chronic Methanol Feeding Led to Memory Impairments and Tau Hyperphosphorylation in Mice

Abstract: Although methanol toxicity is well known for acute neurological sequelae leading to blindness or death, there is a new impetus to investigate the chronic effects of methanol exposure. These include a recently established link between formaldehyde, a methanol metabolite, and Alzheimer's disease (AD) pathology. In the present study, mice were fed with methanol to revisit the chronic effects of methanol toxicity, especially as it pertains to AD progression. Three groups of mice (n = 9) were given either water as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…The metabolism of methanol and formaldehyde in brain cells is important for the function of this vital organ (472). Moreover, the elevation of brain formaldehyde levels is likely to result in neurodegenerative diseases (386,448,450,463,464,517,518). Methanol and the products of its metabolism in brain cells may be synthesized in situ or be introduced from peripheral organs via the bloodstream by overcoming the blood-brain barrier.…”
Section: Features Of Methanol Metabolism In the Brain And In Embryosmentioning
confidence: 99%
“…The metabolism of methanol and formaldehyde in brain cells is important for the function of this vital organ (472). Moreover, the elevation of brain formaldehyde levels is likely to result in neurodegenerative diseases (386,448,450,463,464,517,518). Methanol and the products of its metabolism in brain cells may be synthesized in situ or be introduced from peripheral organs via the bloodstream by overcoming the blood-brain barrier.…”
Section: Features Of Methanol Metabolism In the Brain And In Embryosmentioning
confidence: 99%
“…164 In addition, they found formaldehyde, rather than methanol or the methanol end product formic acid, led to Tau hyperphosphorylation in mouse embryonic cerebral cortex neurons and mouse neuroblastoma N2a cells. 165 The same group also reported that spatial working memory impairments, increased Tau phosphorylation and neuronal loss, accompanied by the presence of Aβ + neuritic-like plaques and NFT-like formations were observed in the brain from young rhesus macaques (5-8 years old) intracerebroventricularly injected formaldehyde for 12 months. 166 Given that the brains of humans and NHPs have considerable similarities in their overall architecture and functional network organization, the NHPs AD model is likely to greatly improve our understanding of the pathogenesis of AD and bring about effective development of therapeutics.…”
Section: Nhps: a Bridge Between Rodents And Humans?mentioning
confidence: 88%
“…During aging, chronic accumulation of endogenous FA is thought to be a risk factor for sporadic age-related dementia [10, 28]. Furthermore, excess FA has been found to contribute to the pathological aggregation of amyloid fragments and tau hyperphosphorylation in normal adult mice and monkeys [29, 30]. More importantly, a direct intracerebroventricular injection of excess FA into animal models causes memory decline [1315].…”
Section: Discussionmentioning
confidence: 99%